CAR-NK cell therapy for glioblastoma: what to do next? - Xiong, Qi; Zhu, Jiao; Zhang, Yong; Deng, Hongxin (Frontiers in Oncology, 2023)
Glioblastoma is a malignant tumor with the highest morbidity and mortality in the central nervous system. Conventional surgical resection combined with radiotherapy or chemotherapy has a high recurrence rate and poor prognosis. The 5-year survival rate of patients is less than 10%. In tumor immunotherapy, CAR-T cell therapy represented by chimeric antigen receptor-modified T cells has achieved great success in hematological tumors. However, the application of CAR-T cells in solid tumors such as glioblastoma still faces many challenges. CAR-NK cells are another potential adoptive cell therapy strategy after CAR-T cells. Compared with CAR-T cell therapy, CAR-NK cells have similar anti-tumor effects. CAR-NK cells can also avoid some deficiencies in CAR-T cell therapy, a research hotspot in tumor immunity. This article summarizes the preclinical research status of CAR-NK cells in glioblastoma and the problems and challenges faced by CAR-NK in glioblastoma.